Fertility Trends in Bangladesh Employing Parity Progression Ratios - Hossain, Md Mowazzem; Islam, Md Nurul; Shah, Md Asaduzzaman; Hossain, Md Golam; Al Mamun, Abu Syed Md; Mondal, Md Nazrul Islam (International Journal of Statistical Sciences, 2024)
Fertility trends in Bangladesh have long been a subject of study due to the country's significant demographic transitions over the past few decades. This study investigated cohort fertility rates and trends using information from the Bangladesh Demographic and Health Surveys (BDHSs) (BDHS 2011, BDHS 2014, and BDHS 2017-2018). The study utilizes parity progression ratios (PPRs) to examine the fertility distribution among all women and currently married women. Fertility patterns are investigated across various birth cohorts of women spanning seven age groups (15-19, 20-24, 25-29, 30-34, 35-39, 40-44, and 45-49), including the entirety of the reproductive age range (15-49 years). In the BDHS 2011, the cohort total fertility rate (TFRc) was 2.62 for all women and 2.73 for currently married women. In the BDHS 2014, the TFRc for all women decreased to 2.40, and for currently married women, it declined to 2.56. Finally, in the BDHS 2017-18, the TFR for all women decreased to 2.30, while for currently married women, it reached 2.45. Notably, TFRc exhibited a declining trend over the three surveys, with the TFR remaining constant at 2.30 from BDHS 2011 to BDHS 2017-18. It is worth mentioning that while the TFR and TFRc values are identical, the TFRc for currently married women in BDHS-2017-18 is slightly higher by 0.15 compared to all women (BDHS 2014). This research highlights significant shifts in cohort fertility levels in Bangladesh over time, offering valuable insights into fertility patterns among women of varying age groups within the reproductive span. The observed declines in both TFRc underscore Bangladesh’s evolving fertility dynamics. Policymakers should sustain declining fertility rates while balancing population control with development and regularly monitor trends to adapt policies to changing reproductive patterns. International Journal of Statistical Sciences Vol. 24(2), November, 2024, pp 1-18